The mycobiome in human cancer: analytical challenges, molecular mechanisms, and therapeutic implications - Ting Ding; Chang Liu; Zhengyu Li (Molecular Cancer)
Abstract The polymorphic microbiome is considered a new hallmark of cancer. Advances in High-Throughput Sequencing have fostered rapid developments in microbiome research. The interaction between cancer cells, immune cells, and microbiota is defined as the immuno-oncology microbiome (IOM) axis. Fungal microbes (the mycobiome), although representing only ∼ 0.1-1% of the microbiome, are a critical immunologically active component of the tumor microbiome. Accumulating evidence suggests a possible involvement of commensal and pathogenic fungi in cancer initiation, progression, and treatment responsiveness. The tumor-associated mycobiome mainly consists of the gut mycobiome, the oral mycobiome, and the intratumoral mycobiome. However, the role of fungi in cancer remains poorly understood, and the diversity and complexity of analytical methods make it challenging to access this field. This review aims to elucidate the causal and complicit roles of mycobiome in cancer development and progression while highlighting the issues that need to be addressed in executing such research. We systematically summarize the advantages and limitations of current fungal detection and analysis methods. We enumerate and integrate these recent findings into our current understanding of the tumor mycobiome, accompanied by the prospect of novel and exhilarating clinical implications.